2004
DOI: 10.1063/1.1780419
|View full text |Cite
|
Sign up to set email alerts
|

Shock Sensitivity of LX-04 Containing Delta Phase HMX at Elevated Temperatures

Abstract: LX-04 is a widely used HMX-based plastic bonded explosive, which contains 85 weight % HMX and 15 weight % Viton binder. The sensitivity of LX-04 to a single stimulus such as heat, impact, and shock has been previously studied. However, hazard scenarios can involve multiple stimuli, such as heating to temperatures close to thermal explosion conditions followed by fragment impact, producing a shock in the hot explosive. The sensitivity of HMX at elevated temperatures is further complicated by the beta to delta s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 3 publications
0
17
0
Order By: Relevance
“…al [4] recently reported that detonation velocity of thermally damaged LX-04 was 7.7 to 7.8 mm/µs, about 10% lower than that (8.5 mm/µs) of pristine highdensity LX-04. Detonation energy density for the damaged LX-04 was 6.5 kJ/cm 3 , much lower than the detonation energy density of 8.1 kJ/cm 3 for the pristine high density LX-04. The break-out curves for the detonation fronts showed that the damaged LX-04 had longer edge lags than the pristine high density LX-04, indicating that the damaged explosive was less ideal.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…al [4] recently reported that detonation velocity of thermally damaged LX-04 was 7.7 to 7.8 mm/µs, about 10% lower than that (8.5 mm/µs) of pristine highdensity LX-04. Detonation energy density for the damaged LX-04 was 6.5 kJ/cm 3 , much lower than the detonation energy density of 8.1 kJ/cm 3 for the pristine high density LX-04. The break-out curves for the detonation fronts showed that the damaged LX-04 had longer edge lags than the pristine high density LX-04, indicating that the damaged explosive was less ideal.…”
Section: Introductionmentioning
confidence: 93%
“…The High Explosives Applications Facility (HEAF) at Lawrence Livermore National Laboratory is a state-of-the-art facility and is dedicated to energetic materials R&D. It is equipped with many sophisticated devices, equipment, and instruments that offer means for diagnostics and characterization of energetic materials as listed in Table 1. Results of damaged material characterization for LX-04 and LX-10 have been reported elsewhere [1,2,3,4]. One dimensional time to explosion system Thermal kinetics 4" Gun for high-velocity impacting Run distance to detonation (Pop-plot)…”
Section: Characterization Of Damaged Energetic Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior experiments on LX-10 (95% HMX, 5% Viton by weight) have been performed [1,2], but the pressure regime of these experiments was limited and questions existed on the extrapolation to lower pressures. Other HMX explosives have also been studied [3] including some common explosives such as PBX 9501 [4,5] and LX-04 [6,7] using wedge tests, electromagnetic velocity gauges, manganin gauges at ambient and elevated temperatures. In this work, the shock sensitivity of LX-10 was measured using in-situ pressure gauges and modeled using Ignition and Growth.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, investigating the effect of temperature on the shock sensitivity of CL-20 is important for explosive design and safety analysis; moreover, the temperature-dependent shock initiation characteristics of CL-20 have not been thoroughly studied. Previous investigations have shown that increasing the temperature of explosive materials affects their shock sensitivity in two ways: by an increase in the porosity, which is attributed to thermal expansion [4], and by transformation of polymorphs that occurs at higher temperatures, a phase transition that can lead to a change in shock sensitivity [5].…”
mentioning
confidence: 99%